Green Finance And Green Sukuk As Environmental Responsibility: Current Issues And Future Challenges - Nugroho, Moh Agus; Fadhilah, Nurul; Okeke, Frankline C.S.A (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2024)
This study attempted to find out the research development in the field of green finance and green sukuk as environmental responsibility, especially in Scopus indexed journal using PoP devices. This research conducted bibliometric methods using VOS viewer. The results indicated that the year of research publication, from 2010 to 2022, shows the growth in the number of research publications. The highest number of articles published in 2020 with total publication of 38 articles. This number is quite higher compared to the previous five years. In early 2010, research on green finance and green sukuk as environmental responsibility was less fascinating for researchers to review since there were only 4 research articles published and indexed by Scopus. Topics that still rarely discussed are related to green finance and green sukuk, such as energy, strategy, carbon emission, role, company, financial performance, country and others. The researchers who contributed the most in the field of green finance and green sukuk namely; Azhgaliyeva D (3 articles), Bergset L, Morea D, Naeem Ma, Su Y, Taghizadeh-Hesary F, Yin W, Yuan H, Zhang D, Agyabeng-Mensah Y and Zhang Y. Each of the researcher contributed 2 research articles respectively. Future research should explore the impact of government policies, the role of technology, and the integration of ESG factors in green finance and sukuk.